Targeting Neutrophils for Enhanced Cancer Theranostics. Issue 33 (12th July 2020) - Tang, Longguang; Wang, Zhantong; Mu, Qingchun; Yu, Zhiqiang; Jacobson, Orit; Li, Ling; Yang, Weijing; Huang, Chunming; Kang, Fei; Fan, Wenpei; Ma, Ying; Wang, Maosheng; et al.
Abstract: Improving tumor accumulation and delivery efficiency is an important goal of nanomedicine. Neutrophils play a vital role in both chemically mediating inflammatory response through myeloperoxidase (MPO) and biologically promoting metastasis during inflammation triggered by the primary tumor or environmental stimuli. Herein, a novel theranostic nanomedicine that targets both the chemical and biological functions of neutrophils in tumor is designed, facilitating the enhanced retention and sustained release of drug cargos for improved cancer theranostics. 5‐hydroxytryptamine (5‐HT) is equipped onto nanoparticles (NPs) loaded with photosensitizers and Zileuton (a leukotriene inhibitor) to obtain MPO and neutrophil targeting NPs, denoted as HZ‐5 NPs. The MPO targeting property of 5‐HT modified NPs is confirmed by noninvasive positron emission tomography imaging studies. Furthermore, photodynamic therapy is used to initiate the inflammatory response which further mediated the accumulation and retention of neutrophil targeting NPs in a breast cancer model. This design renders a greatly improved theranostic nanomedicine for efficient tumor suppression, and more importantly, inhibition of neutrophil‐mediated lung metastasis via the sustained release of Zileuton. This work presents a novel strategy of targeting neutrophils for improved tumor theranostics, which may open up new avenues in designing nanomedicine through exploiting the tumor microenvironment. Abstract : A neutrophil‐targeting nanomedicine is developed to enhance tumor accumulation and improve therapeutic efficacy achieved via in situ cross‐linking catalyzed by endogenous myeloperoxidase. In combination with photodynamic therapy, lung metastasis is inhibited by blocking neutrophil recruitment into the lung through sustained release of a 5‐lipoxygenase inhibitor.